Marine turtle hotspots in the Gulf of Mexico and Mesoamerican Reef: Strengthening management and preparedness - Cuevas, Eduardo; Liceaga-Correa, María de los Angeles; Uribe-Martínez, Abigail; Gallegos-Fernández, Sandra A.; Moncada-Gavilán, Félix; González-Díaz-Mirón, Raúl J.; López-Castro, Melania C.; Guzmán-Hernández, Vicente; López, Martha (Frontiers in Marine Science, 2022)
Marine turtles are of the highest ecological concern in terms of conservation and restoration programs and marine territorial ordering. Marine resource-extracting industries have severe negative impacts on their populations and their habitats. Thus, private industries and decision makers require the best and most robust spatially explicit scientific knowledge for a sustainable and responsible operation and government administration. Therefore, the identification of marine turtle hotspots is a strategic milestone for ecosystem management and an integral ecological knowledge about any region. We identified and delimited marine turtle hotspots in the Gulf of Mexico and Mesoamerican Reef. We analyzed satellite-tracked data of 178 individuals belonging to four marine turtle species. We used Brownian bridge movement models to estimate space use surfaces and map algebra to weight and merge layers of multiple species, life stages, and movement phases. The Yucatan Peninsula and central Veracruz in Mexico, along with the Florida Keys and Louisiana coast in the US, harbor the primary hotspots where marine turtles aggregate. We defined four primary hotspots used for migration in the western Gulf of Mexico, around the Yucatan Peninsula, a northern route following the Loop Current, and a southern one towards Gorda Bank, Central America. This study is the largest assessment of marine turtle hotspots in Mexico and Cuba and supports strategies for reinforcing regional management actions for their conservation, as well as a stronger response and preparedness for tackling anthropic threats to these species. This milestone contributes to extending the knowledge frontiers about these species to a new level.